Impact of Educational Summits on Teachers’ Professionalism and Training in Ekiti State - Faremi, Margaret Funke; Alaba, Oladiji Adebola (NIU Journal of Humanities, 2018)
The study investigated the impact of education summit on the teachers’ professionalism, training and retraining in Ekiti State, Nigeria. owing to the hue and cry about the declining nature of the standard of education as portrayed by the results of external examinations of the post primary institutions and the perceived graduate unemployability of various cadres of tertiary institutions in Nigeria as lamented by employers of labour.  various states have been carrying out educational summits to determine the way forward. One of the proffered solutions is the improvement in teachers’ professional development.  This study focused on various education summit in Ekiti State specifically and government policy on how to improve the teachers for high productivity.  The purpose of the study is to investigate whether annual education summit has impact on teachers’ professional development. Three hypotheses were generated for the study on impact of education summit, government policy and teachers’ incentives. Descriptive research of the survey type was used and 200 teachers were sampled including principals. The results of the investigation showed that educational summit has great influence on teachers’ professionalism, training and retraining. In view of the findings, it is recommended that government should continue to encourage teachers’ professional development in various forms. Also, government should continue to evaluate the level of progress and teachers should see it as a matter of duty to develop themselves for effective teaching